Ethnobotanical study of wild edible plants in Derashe and Kucha Districts, South Ethiopia - Kebebew Fassil; Balemie Kebu (BMC, 2006)
Abstract The study discussed ethnobotany of and threats to wild edible plants in Derashe and Kucha Districts, South Ethiopia. Semi-structured interview, field observation, group discussion, market survey, and pair wise ranking were employed to gather ethnobotanical data. The information was collected from informants of three ethnic groups namely, Kusume, Derashe and Gamo people. The study documented 66 edible plant species belonging to 54 genera and 34 families. Of the reported edibles, 83.3% have more than one use categories. Food, medicine, construction/technology, and fuel wood had contributed 79% of the total uses. Of the recorded wild edible plant species, 78.8% were reported to be edible both in normal and food shortage times. Procurement and use of most edibles were found to be age and gender specific. However, species use under various use categories does not vary among the communities (X2 = 3.89, df = 6, α = 0.05 and 1-α = 12.6). The study showed that the majority (62.1%) of the species were collected from wooded grassland/or bush land vegetation type. Pair wise ranking results indicated that agricultural expansion, over stocking/overgrazing, fuel wood collection, and uncontrolled fire setting as principal threats to wild edible plants in the study areas. The findings suggest that (i) Public awareness and community based management need to be encouraged at all levels in order to overcome the threats; (ii) further investigation into nutritional properties of all the species reported; and (iii) Since the species are also nutraceutical, study on the pharmacological attributes would help to understand their medicinal applications. Furthermore, urgent collection of germplasm from areas under human pressure is recommended.